The observable-state model and nonrenormalizable theories - Ardenghi, Juan Sebastian (2013)
The aim of this work is to apply the observable-state model for the quantum field theory of a φ n self-interaction. We show how to obtain finite values for the two-point and npoint correlation functions without introducing counterterms in the Lagrangian. Also, we show how to obtain the renormalization group equation for the mass and the coupling constant. Finally, we find the dependence of the coupling constant with the energy scale and we discuss the validity of the observable-state model in terms of the projection procedure.